Role of the therapeutic bacteria Lactobacillus gasseri to reduce the cholesterol concentration in vitro and in vivo - Ahmad Talal Hekmat (College of Education for Pure Sciences, 2013)
ABSTRACT The study involved isolation and identification of (50) isolates Lactobacillus gasseri from the feces of breastfed neonates aged (1-4 months) in Mosul. The ability of the bacteria to reduce the concentration of total cholesterol and cholesterol associated with high density lipoprotein (HDL) and low density lipoprotein (LDL) were examined in the presence or absence of bile salts and for two periods of incubation (24, 72) hours, the results showed different effects of these isolates, isolate (5) gave the best results compared to the other isolates, in addition the study includes the effect of bacteria in vivo When rabbits were used as laboratory animals, results indicated the role of bacteria in reducing the concentration of total cholesterol and cholesterol associated with low density lipoprotein in the serum and this confirms the therapeutic role of these bacteria.